Prostitution and its new forms and related phenomena against legal provisions - Szota, Paulina (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The publication aims at presenting the phenomenon of prostitution and its forms. The article presents different ways of defining the term of prostitution. The author also described other phenomena and conditions of their development, which take the form of prostitution. The article describes specific provisions of criminal law as well as of international acts that regulate prostitution directly. In summary, the author tried to consider the issues of legal regulations regarding prostitution and its development.